Efforts to Improve Learning Outcomes with Poster Based on Qr-Code on Excression System Materials - Susanti, Mar'atun (FKIP Universitas Muhammadiyah Sukabumi, 2021)
Abstract: This study aims to improve learning outcomes using QR Code-based poster media on the Excretion System in Humans. This type of research is classroom action research using the Hopkins model. Through 2 cycles starting from planning, action, observation, and reflection. The object of the research was 32 students in class 8E. Data collection tools used tests, questionnaires and observation sheets. The results showed that the cognitive value in the pre-cycle activities obtained an average percentage of 16% with the low category, in the first cycle it got an average percentage of 84.8%, and in the second cycle it got 85% in the very good category while the teacher activity in the first cycle obtained The average value is 79% in the good category, the second cycle gets a value of 96% in the very good category and the activities of the students in the first cycle get an average score of 69% in the good enough category, the second cycle gets a value of 94% in the very good category. The results of the questionnaire showed that 77% of students liked poster media with QR codes. Based on these results, it shows that the application of QR Code-based poster media can improve learning outcomes of 8E grade students of SMPN 1 Warungkiara. Keywords: Poster media, QR code, learning outcomes